Creation of p-wave Feshbach molecules in selected angular momentum states using an optical lattice. (28th September 2016) - Waseem, Muhammad; Zhang, Zhiqi; Yoshida, Jun; Hattori, Keita; Saito, Taketo; Mukaiyama, Takashi
Abstract: We selectively create p -wave Feshbach molecules in the m l = ± 1 orbital angular momentum projection state of 6 Li. We use an optical lattice potential to restrict the relative momentum of the atoms such that only the m l = ± 1 molecular state couples to the atoms at the Feshbach resonance. We observe the hollow-centered dissociation profile, which is a clear indication of the selective creation of p -wave molecules in the m l = ± 1 states. We also measure the dissociation energy of the p -wave molecules created in the optical lattice and develop a theoretical formulation to explain the dissociation energy as a function of the magnetic field ramp rate for dissociation. The capability of selecting one of the two closely-residing p -wave Feshbach resonances is useful for the precise characterization of the p -wave Feshbach resonances.